2022
DOI: 10.4081/monaldi.2022.2241
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and atrial fibrillation: novel evidences and insights

Abstract: Atrial fibrillation (AF) is one of the most prevalent rhythm disorders worldwide, with around 37.574 million cases around the globe (0.51 % global population).  Different studies showed a high informative value of different biomarkers, including such related to the systemic inflammation, biomechanical stress and fibrosis. In this review article we aimed to study only the relation of homocysteine to the AF development. Homocysteine is a sulfur-containing amino acid, that is produced in the process of methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 7 When the level of Hcy increases abnormally, it leads to hyperhomocysteinemia (HHcy). HHcy has been indicated as a risk factor for a variety of disorders, such as cardiovascular diseases, 8 , 9 , 10 neural tube defects, 11 , 12 atrial fibrillation, 13 , 14 Alzheimer's disease, 15 , 16 cancer, 17 , 18 multiple sclerosis, 19 , 20 , 21 migraine, 22 , 23 and other diseases. Additionally, recent evidence showed that HHcy contributed to the development of PD.…”
Section: Introductionmentioning
confidence: 99%
“… 7 When the level of Hcy increases abnormally, it leads to hyperhomocysteinemia (HHcy). HHcy has been indicated as a risk factor for a variety of disorders, such as cardiovascular diseases, 8 , 9 , 10 neural tube defects, 11 , 12 atrial fibrillation, 13 , 14 Alzheimer's disease, 15 , 16 cancer, 17 , 18 multiple sclerosis, 19 , 20 , 21 migraine, 22 , 23 and other diseases. Additionally, recent evidence showed that HHcy contributed to the development of PD.…”
Section: Introductionmentioning
confidence: 99%